2020
DOI: 10.1101/2020.11.25.397323
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RRM2 is a target for synthetic lethal interactions with replication stress checkpoint addiction in high-risk neuroblastoma

Abstract: SummaryNeuroblastoma is a pediatric tumor originating from the sympathetic nervous system responsible for 10-15 percent of all childhood cancer deaths. Half of all neuroblastoma patients present with high-risk disease at diagnosis. Despite intensive multi-modal therapies nearly 50 percent of high-risk cases relapse and die of their disease. In contrast to the overall paucity of mutations, high-risk neuroblastoma nearly invariably present with recurrent somatic segmental chromosome copy number variants. For sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Although earlier studies demonstrated a synergistic effect of triapine with chemotherapeutics or PARP inhibitors in other cancer types (35, 36), we did not observe marked synergy with these drug combinations in EwS cells, which may indicate tumor-specific effects with combinatorial drug applications. Importantly, similar to a very recent report in neuroblastoma (37), we noted a strong synergistic effect of triapine with CHEK1 or WEE1 inhibitors in EwS cells.…”
Section: Discussionsupporting
confidence: 92%
“…Although earlier studies demonstrated a synergistic effect of triapine with chemotherapeutics or PARP inhibitors in other cancer types (35, 36), we did not observe marked synergy with these drug combinations in EwS cells, which may indicate tumor-specific effects with combinatorial drug applications. Importantly, similar to a very recent report in neuroblastoma (37), we noted a strong synergistic effect of triapine with CHEK1 or WEE1 inhibitors in EwS cells.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, a zebrafish MYCN/RRM2 co-overexpression model revealed a strong increase in tumor penetrance compared to MYCN only overexpressing animals. Finally, we demonstrated synergism for combined RRM2 and CHK1 inhibition thus pointing towards this drug vulnerability as an important future angle for therapeutic exploration [125].…”
Section: Rrm2mentioning
confidence: 81%
“…We recently identified the RRM2 gene as target for focal gains and amplifications in high-risk NBs, amongst others resulting from chromothripsis [125]. RRM2 encodes for the 'ribonucleotide reductase regulatory subunit 2 (RRM2) and together with RRM1 forms the RNR ribonucleotide reductase enzyme that ensures dNTP production essential for DNA replication and repair.…”
Section: Rrm2mentioning
confidence: 99%
See 2 more Smart Citations